The influence of legal compliance in farmer group on the growth and development of sustainable mangrove ecosystem - E.K. Purwendah; N.A. Sasongko; H. Susanto; R. Mawardi; T. Cahyono; H.L. Susilawati; T. Wahyuni; D. Juhandi; T. Rahman; A. Gustina; I.D.S. Triana; E. Pudyastiwi; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The limited role of law enforcement agencies in the vast area provides opportunities for local community to contribute to mangrove ecosystem protection. This study emphasizes the importance of sustainable legal adherence by mangrove farmer groups in protecting the ecosystem through self-defence or community policing. It is essential for farmer groups to work together with legal institutions in order to defend the mangrove ecosystem from potential harm. This study seeks to resolve legal uncertainties related to the regulation of natural resources. Legal protection is crucial to ensure sustainability of mangrove ecosystem.METHODS: This study used multi-aspect sustainability analysis and normative-empirical legal methods. Primary data were collected by administering questionnaires and engaging in discussions with the Krida Wana Lestari Farmer Group community in Ujung Alang, Cilacap, Central Java. The data obtained from questionnare was assessed for its sustainability through the application of Multi-Aspect Sustainability Analysis. The analysis of sustainability value, which significantly impacts legal compliance in the future, was conducted using secondary data in the form of legal materials. This enabled the identification of priority areas for improvement.FINDINGS: Legal ambiguities in the protection and supervision of mangrove ecosystem require the participation of the Krida Wana Lestari Farmer Group community. Mangrove management involves the planting of seedlings and their subsequent utilization. Ecosystem protection is ensured through monitoring efforts within the Segara Anakan mangrove area, as well as through informal sanctions imposed by the local community in collaboration with the Nature Conservation Agency and the Village Trustee Non-Commissioned Officer.CONCLUSION: The limited role of law enforcement agencies provides opportunities for community to contribute to the protection. The role in conducting Jagawana Swakarsa (Community-based self-funded Forest Rangers) or community policing is crucial for sustainable mangrove ecosystem management. The engagement of farmer groups exemplifies the application of indigenous wisdom in preserving the environment, which is presently not regulated by the prevailing legal framework.  The mangrove ecosystem provides farmers with economic benefits that contribute to their livelihoods. Not only do farmers have a strong social connection to the mangroves as their place of residence, but they also hold a political stake in ensuring the survival of these valuable ecosystems. Benefits, management, and monitoring aspects scored 100, 94.5, and 100, respectively. Sanctions aspect is sustainable with a score of 65 because forest guards and the authorities enforce forest destruction laws. Through their collaboration with the forestry police, they initiated community-driven endeavors. This united community plays a crucial role in enabling law enforcement to independently safeguard mangroves. The organizational significance lies in prioritizing regional law enforcement and fostering inclusive and comprehensive communication with the community.